Calibration and sensitivity analysis of a novel water flow and pollution model for future city planning: Future Urban Stormwater Simulation (FUSS). (8th February 2022) - Prodanovic, V.; Jamali, B.; Kuller, M.; Wang, Y.; Bach, P. M.; Coleman, R. A.; Metzeling, L.; McCarthy, D. T.; Shi, B.; Deletic, A.
Abstract: Planning for future urban development and water infrastructure is uncertain due to changing human activities and climate. To quantify these changes, we need adaptable and fast models that can reliably explore scenarios without requiring extensive data and inputs. While such models have been recently considered for urban development, they are lacking for stormwater pollution assessment. This work proposes a novel Future Urban Stormwater Simulation (FUSS) model, utilizing a previously developed urban planning algorithm (UrbanBEATS) to dynamically assess pollution changes in urban catchments. By using minimal input data and adding stochastic point-source pollution to the build-up/wash-off approach, this study highlights calibration and sensitivity analysis of flow and pollution modules, across the range of common stormwater pollutants. The results highlight excellent fit to measured values in a continuous rainfall simulation for the flow model, with one significant calibration parameter. The pollution model was more variable, with TSS, TP and Pb showing high model efficiency, while TN was predicted well only across event-based assessment. The work further explores the framework for the model application in future pollution assessment, and points to the future work aiming to developing land-use dependent model parameter sets, to achieve flexibility for model application across varied urban catchments. HIGHLIGHTS: Model used simple urban form to explore temporal + spatial flow + pollution dynamics across catchment. Robust + accurate flow model, effective impervious factor as parameter. Flow-correlated pollutants estimated on subdaily time step. Total nitrogen + E. coli predicted acceptably on event-based assessment due to stochastic impact of human activity. Potential land-use-based calibration + use of pollution model on catchments